2020
DOI: 10.1071/ah19247
|View full text |Cite
|
Sign up to set email alerts
|

Economic and clinical outcomes of the nurse practitioner-led Sydney Adventist Hospital Community Palliative Care Service

Abstract: ObjectiveThe aim of this study was to assess the clinical, economic and personal impacts of the nurse practitioner-led Sydney Adventist Hospital Community Palliative Care Service (SanCPCS) MethodsParallel economic analysis of usual care was conducted prospectively with patients from the enhanced SanCPCS. A convenient retrospective sample from the initial service was used to determine the impact of the enhanced service on patient care. A time series survey was used with patients and carers from within the expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Four studies specifically looked at various nurse-led programme roles. Of these, the studies examining quality of life reported no improvements from such programmes [ 64 , 65 ]. One study noted improvements in home deaths [ 64 ], while another reported no change in this outcome [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies specifically looked at various nurse-led programme roles. Of these, the studies examining quality of life reported no improvements from such programmes [ 64 , 65 ]. One study noted improvements in home deaths [ 64 ], while another reported no change in this outcome [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, the studies examining quality of life reported no improvements from such programmes [ 64 , 65 ]. One study noted improvements in home deaths [ 64 ], while another reported no change in this outcome [ 66 ]. Similarly, hospital utilisation rates did not improve for two of the nurse-led programmes studied [ 64 , 67 ] but did in another study [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…APRNs improve outcomes and enhance the financial value of health care (Coventry et al, 2017; Dubree et al, 2015; Moreton et al, 2020). APRN participation in shared governance helps organizations contain costs through improved role utilization, quality care, and job satisfaction (Condit & Hafeman, 2019; Proulx, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yet hospitals with moderate-to-high nursing engagement demonstrate statistically significant improvements in job satisfaction, retention, patient experience, and burnout (Kutney-Lee et al, 2016). Advanced practice registered nurses (APRNs), inclusive of NPs, certified registered nurse anesthetists (CRNAs), clinical nurse specialists, and certified nurse midwives, are essential health care partners in the efforts of health care organizations to provide cost-efficient and high-quality care that improves patient access, outcomes, and experience (Aiken et al, 2021; Coventry et al, 2017; Htay & Whitehead, 2021; Moreton et al, 2020). However, the ability of APRNs to deliver highly specialized care also makes their turnover's financial and experiential costs extensive and disruptive to patient operations (Arthur et al, 2020; Han et al, 2018; Hartsell & Noecker, 2020).…”
mentioning
confidence: 99%